A Critical Multimodal Discourse Analysis of A Cocomelon Song Entitled "Head, Shoulders, Knees, and Toes": Exploring Its Potential in Stimulating Children's Speaking Skills - Kartika Puji Lestari; Siti Masrifatul Fitriyah; Aan Erlyana Fardhani (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study was conducted with the aim of examining in more depth the children's song on the very famous and widely loved Cocomelon YouTube channel entitled "Head, Shoulders, Knees, and Toes". In addition, this song is also widely listened to by children because of its effectiveness in acting as a learning medium. Therefore, this study is present to analyze in more detail how the song is able to construct multimodal meaning and how this construction is able to stimulate opportunities to speak for children. Furthermore, this song title was chosen because of the researcher's curiosity regarding how the video integrates various multimodal elements to facilitate early vocabulary learning and achieve successful verbal production, which is still unknown due to the lack of research that touches on this. Through the implementation of a multimodal critical discourse analysis, ten scenes from the video were obtained that met the research criteria. Afterward, lyrics, visuals, gestures, audio-musical elements, and multimodal meanings became coding elements for the ten scenes that appeared. These findings provide evidence that the synchronization that occurs in each multimodal significantly strengthens realized vocabulary understanding while providing a space that minimizes anxiety and is supported by rhythm for natural imitation, repetition, and verbal responses. Overall, through this study, it can be concluded that multimodal music videos provide a meaningful scaffold to facilitate the development of early EFL speaking skills and suggest their substantial use to suit their learning objectives in young learner classrooms.